Coins, trade, and the state economic growth in early medieval Japan - Segal, Ethan Isaac (Harvard East Asian Monographs, 2011)
Ethan Isaac Segal highlights the role of peripheral elites- including merchants, warriors, rural estate managers, and religious leaders- in the development of the medieval Japanese economy. Individuals from these groups devised new ways to circumvent older forms of exchange by importing Chinese currency, trading in local markets, and building an effective system of long-distance money remittance. Over time, the central government recognized the futility of trying to stifle these developments, and by the sixteenth century it came to assert greater control over monetary matters throughout the realm. Drawing upon diaries, tax ledgers, temple records, and government decrees, this study chronicles how the circulation of copper currency and the expansion of trade led to the start of a market-centered economy and laid the groundwork for Japan's transformation into an early modern society. -- Book Jacket